Perbedaan komunikasi antar kebudayaan yang berbeda - Innaka Fhatarani Batubara (IICET (Indonesian Institute for Counseling, Education and Therapy), 2017)
intercultural communication in Indonesia is very important because in reality the life of society and culture of Indonesia is very heterogeneous consisting of various tribes, language, religion, race, culture, and custom.